Dynamic biomass char porosity during gasification: Model compared with data. (15th March 2023) - Wu, Ruochen; Baxter, Larry L.
Abstract: This investigation presents a new biomass char porosity model as a function of char conversion during gasification and compares it with entrained-flow data from poplar, corn stover and switchgrass particles reacting with H2 O, CO2, and combinations of both at temperatures of 1050–1350 °C. The experimental data include particle temperature, mass, size, and shape combined with porosity, BET surface area, geometric specific surface area and SEM images of char vascular structure. The new theoretical model describes char porosity changes during char conversion and the model indicates that porosity increases monotonically, consistent with the data. The vascular char structure remains intact even at the highest conversions and this structure effectively transports reactants and products through the particle, with reactions occurring on the walls of these vascular vessels, referred to here as vascules. The investigation shows that char porosity most strongly depends on average vascule diameter which, in turn, increases with increasing conversion. This investigation extends current understanding of the mechanism of heterogeneous biomass char reactions (gasification and oxidation) under kinetically controlled conditions. This work concludes that (1) kinetically controlled biomass gasification involves reactions on the walls of vascules with small contributions from the nanopores or even mesopores; (2) char porosity increases monotonically with increasing char conversion in the kinetically and internal transport-controlled regimes; and (3) observed porosity behaviors correspond the predicted behaviors. Highlights: Dynamic model describes char particle porosity as a function of time/conversion. Porosity increases as vascular structure channels widen, not as small pore growth. Results cover a wide range of size, temperature, and reactant concentrations. Model predictions and conceptual framework agree with available data.